2019
DOI: 10.1002/pc.25403
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of wollastonite reinforced thermoplastic composites: A review

Abstract: Wollastonite is a functional filler that has great potential to be used in thermoplastic composites, replacing more expensive reinforcement such as glass fiber. Wollastonite-reinforced polymer composite materials have attracted the attentions from research field and industries due to their biocompatibility and reinforcing ability in polymers. Due to the relatively high aspect ratio and hardness, wollastonite is able to improve the tensile and flexural strength of polymer composites. Many researches have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 94 publications
(148 reference statements)
0
43
0
Order By: Relevance
“…The structure of CaSiO3 particles, namely their aspect ratios, depends not only on natural conditions but also largely on the preparation and size reduction techniques used. The mechanical properties such as tensile and flexural strengths of CaSiO3 filled polypropylene composites are widely studied and usually an improvement was obtained for untreated and treated CaSiO3 (Chan et al, 2020). In addition, for polypropylene/wollastonite composites the studies were mainly focused on the determination of the adhesion parameters such as the work of adhesion and interfacial free energy of the composites (Svab et al, 2005;Svab et al, 2007;Svab et al, 2009).…”
Section: Literature Surveymentioning
confidence: 99%
“…The structure of CaSiO3 particles, namely their aspect ratios, depends not only on natural conditions but also largely on the preparation and size reduction techniques used. The mechanical properties such as tensile and flexural strengths of CaSiO3 filled polypropylene composites are widely studied and usually an improvement was obtained for untreated and treated CaSiO3 (Chan et al, 2020). In addition, for polypropylene/wollastonite composites the studies were mainly focused on the determination of the adhesion parameters such as the work of adhesion and interfacial free energy of the composites (Svab et al, 2005;Svab et al, 2007;Svab et al, 2009).…”
Section: Literature Surveymentioning
confidence: 99%
“…The introduction of wollastonite in polymeric materials is primarily aimed at improving the mechanical properties of PCM such as elastic modulus, yield strength, and elongation at break, which have a strong effect on the resistance to mechanical deformation [39]. A high ratio of wollastonite grain length to diameter provides better load stress transfer from the polymer matrix to the filler when exposed to an external load, which leads to an increase in the mechanical properties of PCMs [38,[40][41][42]. PCMs containing wollastonite are used in many industries, covering a wide range of products: from thermoset and thermoplastic materials and products to automotive and aerospace products.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the effectiveness of using wollastonite (calcium monosilicate Ca 6 Si 6 O 18 with a theoretical composition, wt.%: CaO—48.3, SiO 2 —51.7 [ 25 , 26 , 27 , 28 , 29 ]) to increase the strength and durability of PCM [ 30 , 31 , 32 , 33 , 34 ]. Wollastonite is used in various high-tech fields including the ceramics and polymer industry [ 35 , 36 , 37 , 38 ]. The use of wollastonite as a filler in PCM is associated with its reinforcing effect on the polymer matrix, chemical inertness, high melting point, and environmental friendliness [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kausch et al, for example, found a strong increase in stiffness when adding alumina to polystyrene [ 1 ]. If surface treatment is performed correctly, mineral fillers can also increase the strength of a polymer matrix [ 2 ]. As a result of the reduced chain mobility, improvements were also found in the long-term creep behaviour [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%